Accentuating the Queer: An Examination of How LGBT Websites Framed the 2012 Presidential Election. (December 2014) - Miller, Brandon
Much research has looked at the framing of political issues and events in the mainstream media. Little work, however, has focused on the framing of these issues in alternative media; and no study to date has examined political framing in lesbian, gay, bisexual, and transgender (LGBT) publications. This study explores the framing of political content through a distinctively queer lens. A thematic analysis was conducted on articles from three online LGBT news outlets to investigate how the queer news media framed the 2012 presidential election. The following four distinctive themes emerged: the creation of a gay angle without obvious gay content, the idea of 2012 being a historic election year for LGBT people, a sense of community between journalist and readers, and a focus on marriage equality above all else. A uniquely queer frame was identified as being central to the coverage of the election, the candidates, and all things political.